IFT20 Mediates the Transport of Cell Migration Regulators From the Trans-Golgi Network to the Plasma Membrane in Breast Cancer Cells - Yang, Huihui; Zhang, Fan; Long, Huan; Lin, Yiwen; Liao, Jiahui; Xia, Haibin; Huang, Kaiyao (Frontiers in Cell and Developmental Biology, 2021)
IFT20 is a subunit of the intraflagellar transport (IFT) system essential for the formation and function of cilia. Besides predominant research in the cilia field, some IFT subunits perform extraciliary roles in non-ciliated cancer cells. However, the specific roles of IFT subunits in tumorigenesis remain unknown. Here, we found that knockout of IFT20 in mouse breast cancer cells lacking primary cilia promoted epithelial mesenchymal transitions (EMTs), active lamellipodia formation, and cell migration. IFT20 localized at the trans-Golgi and trans-Golgi network (TGN), and displayed vesicular co-distributions with Rab8a, the marker of TGN-to-plasma membrane vesicular trafficking. Proximity-dependent biotin identification (BioID) and colocalization analyzes showed that Numb and Ctnnal1, whose depletion promoted cell migration, co-localized with IFT20 at the trans-Golgi/TGN or intracellular transport vesicles. Furthermore, Strep-Tactin pulldown assays revealed an interaction between IFT20 and Ctnnal1 or Numb. Loss of IFT20 lowered the expression of actin-associated Tagln2, whose knockdown promoted cell migration. Thus, the extraciliary function of ITF20 in breast cancer cell was associated with the negative regulation of migration.